Design Liability in the UAE Construction Industry - O’REILLY, BRIAN (2022)
This dissertation explores design liability in the UAE construction industry. First and foremost, design liability in the UAE is a matter of contract between the parties to a construction contract, however, the terms and conditions if the contract are also subject to the laws of the UAE. In addition to discussing the current outlook for the UAE construction industry, this dissertation will examine the principles governing the formation and performance of a construction contract and the level of design liability that the parties normally assume. This will be examined in accordance with the laws of the UAE governing contracts. Not only do parties execute construction contracts in accordance with contract law, but the parties are also subject to laws governing delict and the provisions of delict will be examined with respect to the parties’ design liabilities and the risks and remedies that whilst not always provided for under a contract are important considerations. An important facet of the law which is commonly overlooked in contracts in the UAE concerning design liability is decennial liability and this will be examined in detail and the risks, liabilities, and remedies available under the provisions of the law will be discussed. The model form of contract most widely used in the UAE will be reviewed in relation to contract law, liability for delict and decennial liability. The model form of contract will be discussed to determine if the provisions of the law are well considered and if any inconsistencies can be identified.